Noradrenaline Triggers Multivesicular Release at Glutamatergic Synapses in the Hypothalamus - Gordon, Grant R. J. (J Neurosci, 2005)
The origin of large-amplitude miniature EPSCs (mEPSCs) at central synapses remains to be firmly established. Here, we show that at excitatory synapses onto magnocellular neurosecretory cells in the hypothalamus, noradrenaline induces a rapid and robust increase in mEPSC amplitude that requires α(1)-adrenoceptor activation but is impervious to postsynaptic manipulations that block the putative insertion of AMPA receptors. In response to noradrenaline, mEPSCs exhibit a putative multimodal amplitude histogram distribution that is not attibutable to random temporal summation, the unveiling of a quiescent synapse, or the release of large vesicles. Large-amplitude mEPSCs are sensitive to a high dose of ryanodine and are associated with an enhanced glutamate cleft concentration. Together, these data are consistent with the hypothesis that large-amplitude mEPSCs result from the synchronous release of multiple vesicles via rapid presynaptic calcium expulsion from intracellular stores.